Three-Dimensionally Printed Interconnects for Smart Contact Lenses - Kim, Hyungjoo; Kim, Jinseok; Kang, Jaheon; Song, Yong-Won (American Chemical Society, 2018)
One of the ultimate wearable heath-monitoring gears, smart contact lens, requires miniaturized devices compounded and interconnected with each other on the lens for a successful system functioning. Because of the different device thickness, the interconnect patterns need to be three-dimensional (3D) conforming the steps given by the diversified on-lens devices. Also, the patterns should be low-temperature processed and flexible considering the mechanical and thermal property of the lens material. We demonstrate the 3D interconnects electrosprayed on a contact lens platform with Ag-Ag nanowire (NWs) composite ink conforming the steps. Quantitative and informative analysis on the interconnects is presented. Thick polyimide film (12.5 mu m) in C-shape is employed as a primary substrate to form the 3D patterns that is to be transferred onto the contact lens. The AgNWs act as frames to support the Ag ion inks printed across the steps. The resultant interconnects realized with the Ag/AgNW composite ink with 0.3 wt % AgNW have the sheet resistance (R-s) of 0.396 Omega/square spanning the height difference of 300 mu m. AgNWs also provide durability to the patterns against crack formation and propagation under significant device deformation. Unlike pure Ag pattern which shows the R-s changes of 86.1% in the bending condition, the optimally formulated composite pattern shows the suppressed R-s change of only 15.2% with a bending radius of 3 mm.
Keywords: CONDUCTIVE LINES; ELECTRONICS; PATTERNS; FILM; INK; TECHNOLOGY; SURFACES; GRAPHENE; GLUCOSE